2009
DOI: 10.1152/japplphysiol.91243.2008
|View full text |Cite
|
Sign up to set email alerts
|

Maximal lengthening contractions induce different signaling responses in the type I and type II fibers of human skeletal muscle

Abstract: The molecular mechanisms by which resistance exercise enlarges muscle mass, particularly the mass of fast-twitch type II fibers, are likely to involve enhanced phosphorylation/activation of key enzymes regulating protein synthesis. The hypothesis is that resistance exercise influences the phosphorylation of such key signaling proteins to a greater extent in type II than in type I fibers. Six recreationally active male subjects performed four sets of six maximal lengthening contractions with one leg. Muscle bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 43 publications
4
64
5
Order By: Relevance
“…p38 MAPK is responding to both anabolic (e.g., muscle cell stretch, functional overload) and catabolic stimuli (e.g., tumor necrosis factor α) (21,27,44). In the present study, phosphorylated p38 MAPK was elevated after the resistance loading in line with previous reports in humans (4,19,39,41). Interestingly, these changes, when expressed as groups' means were greater in the morning compared to the afternoon in the present study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…p38 MAPK is responding to both anabolic (e.g., muscle cell stretch, functional overload) and catabolic stimuli (e.g., tumor necrosis factor α) (21,27,44). In the present study, phosphorylated p38 MAPK was elevated after the resistance loading in line with previous reports in humans (4,19,39,41). Interestingly, these changes, when expressed as groups' means were greater in the morning compared to the afternoon in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Previous reports on humans have shown increases (e.g., (8), decreases (7,40) but majority of studies reported no change in Akt phosphorylation after exercise (1,11,18,39,41). It can be speculated that low muscle glycogen levels decrease resistance exercise response of Akt phosphorylation (5), and may be thus the reason for the lack of Akt responses in some individuals in the morning in the present study.…”
Section: Discussioncontrasting
confidence: 52%
“…showed a difference in anabolic response between type‐I and type‐II muscle fibres, with increased AKT phosphorylation and downstream pathway activation in the type‐II fibres 69. In contrast, in COPD, the respiratory muscle with a shift towards more type‐I fibres displayed a larger AKT activation and downstream signalling than the limb muscles with a shift towards more type‐II fibres.…”
Section: New Insights In the Pathophysiology Of Muscle Wasting In Chrmentioning
confidence: 94%
“…Moreover, differences in type I and type II fibers activated in force development influence the phosphorylation of these key signaling proteins [32,46,47].…”
Section: Exercise Training and The Akt-mtor Pathwaymentioning
confidence: 99%